CaO and Graphene Oxide Enhances Drought Stress from Callus Tissues of Medicago Sativa L. Cultivars - YAZICILAR, Büşra; BEZİRGANOGLU, İsmail; CHANG, Yen Ling; NADAR, Muthukumar (Iğdır Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2022)
Drought stress can be described as multidimensional stress factors affecting plants’ growth, development, and productivity. In order to reduce the adverse impact of drought stress, a plethora of attempts have been employed. Among those attempts, nano-engineered particles have gained a remarkable attention. Of the relevant particles, calcium oxide (CaO) and graphene oxide (GO) have been well-documented to positively regulate and mediate the plant growth system through shifting physiological biochemical and molecular aspects of the plant. The solo impacts of the nanoparticles are well-known but their interactions were not assayed for Medicago sativa L. cultivars. For that reason, the present study investigates the impact of CaO NPs and GO on the response and regulation of the defensive mechanism in alfalfa (Medicago sativa L.) callus in drought stress-suffered cultivars. The activation of CaO-GO can be induced with mannitol in the callus of alfalfa cultivars. Dry and fresh weight values were determined in callus samples. There were significant differences between cultivars and concentration. In terms of MDA, H2O2, proline content, it was observed that the Ca2+ NPs application was important, and it showed a strong link with the resistance degree of cultivars. Erzurum cultivar was observed for better proline content with 1.5 ppm GO. MDA activities demonstrated an increasing trend concerning concentrations of mannitol and nanoparticles. The MDA highest activity was observed with 1/2 ppm CaO+0.5/1.5 ppm GO (0.1849 mg/g FW) in the Erzurum. However, the Erzurum cultivar responded with better H2O2 content with 100 mM mannitol +0.5 ppm (0.1017 mg/g FW). This result has presented, under in vitro conditions, that the supplementation of CaO and GO can importantly reduce the negative impacts of drought stress on alfalfa callus; additionally, it has been seen that the dosages of nanoparticle and mannitol are also important.